Leave me alone: solitary females attract more mates in a nocturnal insect. (20th May 2020) - Lehtonen, Topi K; Kaitala, Arja
Abstract: Spatial distributions of sexual competitors and potential mating partners have a large impact on sexual selection and mating systems. Typically, such effects are investigated with regard to male aggregations. However, females may also need to compete for mating opportunities. Here, we investigated the consequences of clustering and rival attractiveness on female mate attraction success under field conditions in a nocturnal beetle, the common glowworm, Lampyrus noctiluca . We placed dummy females of two glow intensity (attractiveness) levels either alone or in clusters of varying attractiveness compositions. We found that, by displaying alone rather than in a cluster, females have a higher probability of mating and greater potential to exercise mate choice. Within clusters, females of both attractiveness levels had the highest probability of mating when having neighbors of only the less attractive type. These results show that both the presence and attractiveness of rivals can strongly influence females' mate attraction. The findings also suggest that the typical distribution of glowing females in the wild is better explained by female than male benefits. Hence, the results highlight the important links between spatial distribution of females, male mate searching, and sexual selection. Abstract : Females, too, may compete for mating opportunities. We show that the presence and attractiveness of rivals impact how successfully females attract mates. In particular, by using artificial glowworm females that attract flying males to mate by glowing during the night, we found that solitary females have more mates than those in a group. Within clusters, females benefit if they only have neighbors with dim glow. Hence, rival presence and attractiveness can influence female mating strategies.